Alterations in CA1 pyramidal neuronal intrinsic excitability mediated by Ih channel currents in a rat model of amyloid beta pathology. (1st October 2015) - Eslamizade, M.J.; Saffarzadeh, F.; Mousavi, S.M.M.; Meftahi, G.H.; Hosseinmardi, N.; Mehdizadeh, M.; Janahmadi, M.
Highlights: Intrafrontal cortex injection of Aβ caused deficits in passive avoidance task. Aβ treatment decreased excitability of CA1 pyramidal cells. Decreased neuronal excitability is due to increased HCN and TRPV1 currents. Aβ treatment caused upregulation of the mRNA of HCN1 channel in CA1 pyramidal layer. Abstract: Amyloid beta (Aβ) accumulation plays an important role in the pathogenesis of Alzheimer's disease (AD) by changing the neuronal excitability. However, the cellular mechanisms by which accumulation of Aβ affects intrinsic neuronal properties are not well understood. The effect of bilateral intra-frontal cortex Aβ (1–42) peptide injection on the intrinsic excitability of hippocampal CA1 pyramidal neurons with particular focus on the contribution of hyperpolarization-activated (Ih) channel currents was examined using whole-cell patch-clamp recording. Passive avoidance memory impairment and morphological changes in rats receiving intra-frontal Aβ treatment were observed, which was associated with significant changes both in passive and active intrinsic electrical membrane properties of CA1 pyramidal neurons. Electrophysiological recording showed a significant decrease in neuronal excitability associated with an augmentation in the first spike after-hyperpolarization (AHP) amplitude. In addition, the depolarizing sag voltage was altered in neurons recorded from Aβ-treated group. In voltage-clamp condition, a hyperpolarizing activated inward current sensitive to ZD7288 and capsaicin was significantly increased in neurons from Aβ-treated rats. The Ih current density was increased and the activation curve was shifted toward less negative potential in the Aβ-treated group as compared to control group. The enhancing effect of Aβ treatment on Ih current was confirmed by showing upregulation of the mRNA of HCN1 channel in the CA1 pyramidal layer of hippocampi. These findings suggest the contribution of Ih and possibly TRPV1 channel currents to the changes induced by Aβ treatment in the intrinsic membrane properties, which, in turn, may provide therapeutic targets for treatment of AD.